Restorative trees revive farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The management of trees for farmland rehabilitation and development was the theme of a seminar organised jointly in Khartoum, Sudan, from 27 October to 7 November 2000 by the National Forests and Agricultural Research Corporations of Sudan